Efektifitas Model Pembelajaran Group Investigation (GI) terhadap Hasil Belajar Materi Sistem Reproduksi Manusia Pada Siswa Kelas IX.1 di SMP Negeri 13 Pekanbaru - Ni Komang Dewi Ratnawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This study aims: 1) To determine the effectiveness of the Group Investigation (GI) model in the subject matter of the human reproductive system in class IX.1 and IX.2 Pekanbaru SMP Negeri 2) To improve the learning outcomes of students in class IX.1 and IX.2 SMP Negeri 13 Pekanbaru is the subject matter of the human reproductive system through the Group Investigation (GI) model. The effectiveness of the Group Investigation (GI) learning model can improve learning outcomes in classes IX-.1 and IX.2 Pekanbaru State Junior High School 13. This situation can be seen from the results of the tests that have been done, obtained the average value for the experimental class is 66.43 lowest value = 50 and the highest value = 97, and students who complete KKM = 27 students and KKM incomplete = 10 students. While the average value of the control class is 54.67 the lowest value = 30 and the highest value = 80, and students who have completed KKM = 9 students and students who have not completed KKM = 27 students. From the analysis of hypothesis testing it is known, that the experimental group is better than the control group. This is indicated by the value of tcount = 5.409. Ho testing criteria is accepted if tcount <t table. The results of the tcount are then consulted with ttable where a = 5%, dk = n1 + n2 - 2 = 85, obtained = 1-α t (0.95) (85) = 1.66. Because in this study tcount = 5.409 and t table = 1.66, and this means tcount <ttable, then Ho is accepted or significant. And the hypothesis that the experimental class learning outcomes are better than the control class, accepted. Thus the learning of material biology in the human reproductive system using the cooperative learning model type Group Investigation (GI), and the hypothesis which states that the experimental class learning outcomes are better than the control class, accepted.